Formation of the definitive endoderm in mouse is a Smad2-dependent process. - Tremblay, K; Hoodless, P; Bikoff, E; Robertson, E (2000)
TGFbeta growth factors specify cell fate and establish the body plan during early vertebrate development. Diverse cellular responses are elicited via interactions with specific cell surface receptor kinases that in turn activate Smad effector proteins. Smad2-dependent signals arising in the extraembryonic tissues of early mouse embryos serve to restrict the site of primitive streak formation and establish anteroposterior identity in the epiblast. Here we have generated chimeric embryos using lacZ-marked Smad2-deficient ES cells. Smad2 mutant cells extensively colonize ectodermal and mesodermal populations without disturbing normal development, but are not recruited into the definitive endoderm lineage during gastrulation. These experiments provide the first evidence that TGFbeta signaling pathways are required for specification of the definitive endoderm lineage in mammals and identify Smad2 as a key mediator that directs epiblast derivatives towards an endodermal as opposed to a mesodermal fate. In largely Smad2-deficient chimeras, asymmetric nodal gene expression is maintained and expression of pitx2, a nodal target, is also unaffected. These results strongly suggest that other Smad(s) act downstream of Nodal signals in mesodermal populations. We found Smad2 and Smad3 transcripts both broadly expressed in derivatives of the epiblast. However, Smad2 and not Smad3 mRNA is expressed in the visceral endoderm, potentially explaining why the primary defect in Smad2 mutant embryos originates in this cell population.